Clinical use of insulin degludec. Issue 1 (July 2015) - Vora, Jiten; Cariou, Bertrand; Evans, Marc; Gross, Jorge Luiz; Harris, Stewart; Landstedt-Hallin, Lena; Mithal, Ambrish; Rodriguez, Martín Rodríguez; Meneghini, Luigi
Highlights: Insulin degludec (IDeg) is a novel basal insulin with improved PK and PD properties. IDeg improves glycaemic control and significantly reduces the risk of hypoglycaemia. When switching to IDeg, this can be done unit-to-unit or may require dose reduction. Dose adjustment with IDeg can be carried out once-weekly in steps of 2 units. The ultra-long duration of action of IDeg allows for dose flexibility, if needed. Abstract: The limitations of current basal insulin preparations include concerns related to their pharmacokinetic and pharmacodynamic properties, hypoglycaemia, weight gain, and perception of management complexity, including rigid dosing schedules. Insulin degludec (IDeg) is a novel basal insulin with improved pharmacokinetic and pharmacodynamic properties compared to insulin glargine (IGlar) including a long half-life of ∼25 h and a duration of action >42 h at steady state, providing a flat and stable blood glucose-lowering effect when injected once daily. Evidence from phase 3a clinical trials with a treat-to-target design in patients with type 1 and type 2 diabetes has shown that IDeg has similar efficacy to IGlar, with a 9% and 26% reduction in risk of overall and nocturnal hypoglycaemia, respectively (in the pooled population) during the entire treatment period, and a 16% and 32% reduction during the maintenance period, respectively. Given its pharmacodynamic properties, IDeg offers a broad dosing window, allowing for flexible dose administration, if required. Two different formulations of IDeg are available (100 units/mL [U100] and 200 units/mL), the latter providing the same IDeg dose as the U100 formulation in half the injection volume. The unique pharmacokinetic profile of IDeg facilitates glycaemic control while minimising the risk of nocturnal hypoglycaemia.